Impact of Massage Therapy and Breathing Techniques on the Satisfaction of Primiparous Women with Childbirth - Arezoo Haseli; Farideh Eghdampour; Ashraf Ghiasi (Mashhad University of Medical Sciences, 2018)
Introduction: In the modern era, global endeavors are made to reduce the rate of cesarean section and encourage natural childbirth, and maternal satisfaction and its dimensions should also be addressed by the governments of developing country. The present study aimed to investigate the impact of massage therapy combined with breathing techniques on the satisfaction of primiparous women with childbirth. Methods: This clinical trial was conducted on 64 primiparous, pregnant women admitted to the obstetrics ward of Lolagar Hospital in Tehran, Iran in 2010. The subjects were divided into two groups of experimental and control via simple random allocation. The experimental group (n=32) received effleurage abdominal massage combined with Lamaze breathing techniques within the first 30 minutes in the active and transition phases of labor. The control group (n=32) received no intervention. Satisfaction with childbirth was measured using Mackey's childbirth satisfaction rating scale. Data analysis was performed in SPSS version 17 using Mann-Whitney U test and independent t-test at the significance of P<0.05. Results: Mean total score of childbirth satisfaction was significantly higher in the experimental group (64.08±5.68) compared to the control group (42.87±7.09) (P<0.001). With the exception of satisfaction with spouse support (P=0.606), significant differences were observed in all the dimensions of childbirth satisfaction between the study groups, including general satisfaction (P=0.01), self-satisfaction (P<0.001), satisfaction with the midwife (P=0.001), and satisfaction with the condition of the neonates (P<0.001). Conclusion: According to the results, abdominal massage therapy with breathing techniques increased the satisfaction of primiparous women with childbirth. Therefore, it is recommended that this non-therapeutic approach be incorporated into labor for desirable delivery.